Feasibility analysis of Kediri - Tulungagung toll - Edna R. Hermansyam; Wahju Herijanto (Journal of Civil Engineering, 2023)
The Kediri-Tulungagung Toll Road is an essential part of the Non-Trans Java Toll Road, which is a national strategic project aimed at facilitating economic activities in the southern part of East Java and improving connectivity to Kediri Airport. This study focuses on analyzing the economic and financial feasibility of the Kediri-Tulungagung toll road development project. The feasibility study involves assessing the project's viability, determining whether it should proceed or be delayed. The analysis includes evaluating traffic volume data, measuring road saturation levels before and after construction, and analyzing the transfer of road users to the toll road. Furthermore, an economic feasibility analysis is conducted to calculate savings in vehicle operating costs and travel time, as well as assess several parameters such as Benefit-Cost Ratio (BCR), Net Present Value (NPV), Internal Rate of Return (IRR), and Payback Period (PbP). Based on JICA 1 modeling and questionnaire responses, calibration values were determined for different vehicle classes. The a value and b value were recalibrated until they reach the appropriate values. The economic feasibility analysis reveals a BCR value of 11,656 (BCR>1), an NPV of IDR 91,043,209,729,042 (NPV>0), and an IRR of 18.3811% (IRR>Interest rate). In the financial feasibility analysis using interest rates as discount rates, the BCR is 6,265 (BCR>1), the NPV is Rp 44,977,644,753,162 (NPV>0), the IRR is 11,872% (IRR>Interest rate), and the Payback Period occurs in the 24th year and 7th month after the toll road's operation. Based on these analyses, the Kediri-Tulungagung Toll Road is deemed economically and financially feasible when using interest rates as the discount rate.